Autonomous CaMKII requires further stimulation by Ca(2+)/calmodulin for enhancing synaptic strength - Barcomb, Kelsey (Federation of American Societies for Experimental Biology, 2014)
A hallmark feature of Ca(2+)/calmodulin (CaM)-dependent protein kinase II (CaMKII) is generation of autonomous (Ca(2+)-independent) activity by T286 autophosphorylation. Biochemical studies have shown that “autonomous” CaMKII is ∼5-fold further stimulated by Ca(2+)/CaM, but demonstration of a physiological function for such regulation within cells has remained elusive. In this study, CaMKII-induced enhancement of synaptic strength in rat hippocampal neurons required both autonomous activity and further stimulation. Synaptic strength was decreased by CaMKIIα knockdown and rescued by reexpression, but not by mutants impaired for autonomy (T286A) or binding to NMDA-type glutamate receptor subunit 2B (GluN2B; formerly NR2B; I205K). Full rescue was seen with constitutively autonomous mutants (T286D), but only if they could be further stimulated (additional T305/306A mutation), and not with two other mutations that additionally impair Ca(2+)/CaM binding. Compared to rescue with wild-type CaMKII, the CaM-binding-impaired mutants even had reduced synaptic strength. One of these mutants (T305/306D) mimicked an inhibitory autophosphorylation of CaMKII, whereas the other one (Δstim) abolished CaM binding without introducing charged residues. Inhibitory T305/306 autophosphorylation also reduced GluN2B binding, but this effect was independent of reduced Ca(2+)/CaM binding and was not mimicked by T305/306D mutation. Thus, even autonomous CaMKII activity must be further stimulated by Ca(2+)/CaM for enhancement of synaptic strength.—Barcomb, K., Buard, I., Coultrap, S. J., Kulbe, J. R., O'Leary, H., Benke, T. A., Bayer, K. U. Autonomous CaMKII requires further stimulation by Ca(2+)/calmodulin for enhancing synaptic strength.